TELAAH NILAI INTI EKONOMI KERAKYATAN - Novianto Putra, Ronny Ersya; Suman, Agus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aim to: a. Assessing patterns of irregularities Pancasila as the philosophy of life in the economically; b. Knowing and reviewing the core value democratic economic Â Methods used are qualitative, with analysis tools library studies. Research results portray: there has been a pattern of aberration Pancasila in neoliberal wisdom economically practices that only benefit the individual andÂ the core values of the mandate UUD 1945 and Soekarno-Hatta thought philosophical excavated for pulcked core of message. Recommendations from the research needed to build the economy of sector development sustainable basis by establishing financial institutions that brought the implementation of core values democratic economy Keyword: Core Values Democratic Economy, Pancasila, Basis sectorÂ Economy, Financial Institutions